2018
DOI: 10.3892/mmr.2018.8447
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of osthole against inflammation induced by lipopolysaccharide in BV2 cells

Abstract: Inflammation and oxidative stress are implicated in the development of neurodegenerative diseases. Osthole is a compound that is extracted from She Chuang Zi, which is a type of traditional Chinese medicine. Osthole has previously been demonstrated to exhibit anticancer activities and has a low toxicity. However, to the best of our knowledge, the anti‑inflammatory effects of osthole in microglial cells have not been investigated extensively. The aim of the present study was to investigate the potential protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Osthole protected against Ang II-induced apoptosis of rat aortic endothelial cells through suppression of NF-κB and activation of Nrf2 and its downstream antioxidant genes and effectively inhibited Keap1, denoting its potential therapeutic effect against vascular injury [244]. In another study, osthole protected against LPS-induced inflammation in BV2 cells via NF-κB suppression and upregulation of the Nrf2/HO-1 pathway dose dependently [245]. Additionally, osthole exerted neuroprotective effects against global cerebral I/R injury by reducing oxidative stress via the upregulation of the Nrf2/HO-1 signaling pathway [246].…”
Section: Fraxin Fraxin (7-hydroxy-6-methoxy-8-[(2s3r4s5s 6rmentioning
confidence: 99%
“…Osthole protected against Ang II-induced apoptosis of rat aortic endothelial cells through suppression of NF-κB and activation of Nrf2 and its downstream antioxidant genes and effectively inhibited Keap1, denoting its potential therapeutic effect against vascular injury [244]. In another study, osthole protected against LPS-induced inflammation in BV2 cells via NF-κB suppression and upregulation of the Nrf2/HO-1 pathway dose dependently [245]. Additionally, osthole exerted neuroprotective effects against global cerebral I/R injury by reducing oxidative stress via the upregulation of the Nrf2/HO-1 signaling pathway [246].…”
Section: Fraxin Fraxin (7-hydroxy-6-methoxy-8-[(2s3r4s5s 6rmentioning
confidence: 99%
“…Osthole (100 and 200 mg/kg) demonstrated protective effects for sepsis-induced acute lung lesions via suppressing the inflammatory reaction, oxidative stress, and cell apoptosis [126]. From in vitro studies, osthole (4, 7 and 10 µg/mL) could shield inflammatory BV2 cells from inflammation-induced by lipopolysaccharide stimulation in the mechanism of inhibition of NF-κB and Nrf2 signaling pathways [127]. Osthole (12.5-100 µmol/L) could dramatically suppress the production of NO, IL-6 and TNF-α and other inflammatory cytokines.…”
Section: Inflammationmentioning
confidence: 99%
“…Anti-fatty liver effect Osthole 10, 20, and 40 mg/kg for 6 weeks via gavage In vivo [117] Anti-fatty liver effect Osthole 10, 20, and 40 mg/kg for 6 weeks via gavage In vivo [118] Anti-fatty liver effect Osthole 0.1 mL/10 g body weight per day for 4 weeks via gavage In vivo [119] Anti-fatty liver effect Osthole 12.5, 25, 50, and 100 µmol/L In vitro [120] Anti-fatty liver effect Osthole 10, 20, and 40 mg/kg for 4 weeks via oral administration In vivo [121] Anti-inflammatory effect Osthole 50 mg/kg via oral administration for 7 days In vivo [122] Anti-inflammatory effect Osthole 10 and 30 mg/kg In vivo [123] Anti-inflammatory effect Osthole 10, 20, and 30 mg/kg via abdominal injection In vivo [124] Anti-inflammatory effect Cnidium Lactone Micro 2, 4, and 8 mg/mL In vivo [125] Anti-inflammatory effect Peroxyauraptenol, auraptenol Peroxyauraptenol:10 µM Auraptenol:100 µM In vitro [126] Anti-inflammatory effect Osthole 40 mg/kg for 4 days via gavage In vivo [127] Anti-inflammatory effect Osthole 100, 200 mg/kg twice a day with 12 h interval via abdominal injection In vivo [128] Anti-inflammatory effect Osthole 4, 7, and 10 µg/mL In vitro [129] Anti-inflammatory effect Osthole 12.5-100 µmol/L In vitro [130] Anti-inflammatory effect Osthole 10 µg/mL In vitro [131] Anti-inflammatory effect 17 Chemical compounds isolated from CMC with voucher number (CM-201010) IC 50 ≤ 7.31 µg/mL for 3 -O-methylmurraol, murraol, xanthotoxin, imperatorin, cnidimol A, IC 50 ≤ 7.83 µg/mL for osthenol, peroxyauraptenol, demethylauraptenol, bergapten, cnidimol A…”
Section: Pharmacological Effects Tested Substance Active Dose/concentmentioning
confidence: 99%
“…Both in vivo and in vitro studies have also shown that Angelica pubescens has effective analgesic and bactericidal effects . Among the components of the herb, ‘osthole’ has been reported as an active component of the anti‐inflammatory action . In addition, Angelica pubescens contains substantial amounts of antioxidants that protect cell components from free radical‐induced damage .…”
Section: Introductionmentioning
confidence: 99%
“…[10] Among the components of the herb, 'osthole' has been reported as an active component of the anti-inflammatory action. [11] In addition, Angelica pubescens contains substantial amounts of antioxidants that protect cell components from free radical-induced damage. [12] However, to the best of our knowledge, the essential oil extracted from the dry rhizomes of Angelica pubescens by hydrodistillation (AO) has not been investigated for its pharmacological activity, particularly with respect to anti-photoaging effects for development of skin care products.…”
Section: Introductionmentioning
confidence: 99%